Heart of darkness: the influence of galactic dynamics on quenching star formation in galaxy spheroids - Gensior, Jindra; Kruijssen, Diederik; Keller, Benjamin W. (Monthly notices of the Royal Astronomical Society, 2020)
Quenched galaxies are often observed to contain a strong bulge component. The key question is whether this reflects a causal connection - can star formation be quenched dynamically by bulges or the spheroids of early-type galaxies? We systematically investigate the impact of these morphological components on star formation, by performing a suite of hydrodynamical simulations of isolated galaxies containing a spheroid. We vary the bulge mass and scale radius, while the total initial stellar, halo, and gas mass are kept constant, with a gas fraction of 5 per cent. In addition, we consider two different sub-grid star formation prescriptions. The first follows most simulations in the literature by assuming a constant star formation efficiency per free-fall time, whereas in the second model it depends on the gas virial parameter, following high-resolution simulations of turbulent fragmentation. Across all simulations, central spheroids increase the gas velocity dispersion towards the galactic centre. This increases the gravitational stability of the gas disc, suppresses fragmentation and star formation, and results in galaxies hosting extremely smooth and quiescent gas discs that fall below the galaxy main sequence. These effects amplifywhen using the more sophisticated, dynamics-dependent star formation model. Finally, we discover a pronounced relation between the central stellar surface density and star formation rate (SFR), such that the most bulge-dominated galaxies show the strongest deviation from the main sequence. We conclude that the SFR of galaxies is not only set by the balance between accretion and feedback, but carries a (sometimes dominant) dependence on the gravitational potential.